POPULASI FUNGI DAN BAKTERI TANAH DI HUTAN PEGUNUNGAN DAN DATARAN RENDAH DI KAWASAN TAMAN NASIONAL LORE LINDU SULAWESI TENGAH - Sahara, Nanang; Wardah, Wardah; Rahmawati, Rahmawati (Universitas Tadulako, 2019)
The microorganisms found in the forest soil are one of the factors that influence the formation of forest soil. In mountain tropical forests slow down soil formation processes as evapotranspiration decreases, chemical reactions are slower and densities of fungi and soil bacteria are fewer, whereas in lowland forests are rich in vegetation species, as well as hot and humid climate conditions. The purpose of this research is to know the population of fungi and bacteria of forest soil of mountains and lowland forest. The study was conducted from December 2017 to February 2018. This research started from field survey, determination of sampling point. Soil sampling was done on a plot with size 25 m × 25 m with a soil depth of 0-10 cm and composite soil sampling. This research uses descriptive analysis method. The results showed that the population of fungi and bacteria are different between the mountain forest (Nokilalaki) and lowland forest (Kamarora). The lowland forest soil higher of fungi (614 × 103 CFU g-1) and bacteria population (43.6 × 106 CFU g-1) then the mountain forest soil of fungi (188.8 × 103 CFU g-1) and bacteria population (7.36 × 106 CFU g-1).